Organ Donation and Transplantation in Canada: Insights from the Canadian Organ Replacement Register. Issue 1 (9th December 2014) - Kim, Sang Joseph; Fenton, Stanley SA; Kappel, Joanne; Moist, Louise M; Klarenbach, Scott W; Samuel, Susan M; Singer, Lianne G; Kim, Daniel H; Young, Kimberly; Webster, Greg; Wu, Juliana; Ivis, Frank; et al.
Purpose of review: To provide an overview of the transplant component of the Canadian Organ Replacement Register (CORR). Findings: CORR is the national registry of organ failure in Canada. It has existed in some form since 1972 and currently houses data on patients with end-stage renal disease and solid organ transplants (kidney and/or non-kidney). The transplant component of CORR receives data on a voluntary basis from individual transplant centres and organ procurement organizations across the country. Coverage for transplant procedures is comprehensive and complete. Long-term outcomes are tracked based on follow-up reports from participating transplant centres. The longitudinal nature of CORR provides an opportunity to observe the trajectory of a patient's journey with organ failure over their life span. Research studies conducted using CORR data inform both practitioners and health policy makers alike. Implications: The importance of registry data in monitoring and improving care for Canadian transplant candidates/recipients cannot be over-stated. This paper provides an overview of the transplant data in CORR including its history, data considerations, recent findings, new initiatives, and future directions.